The Dynamics of the Conceptualization and Categorization of Space in the Russian Language - Romanova, Tatyana (Respectus Philologicus, 2013)
This article presents examples taken from the National corpus of Russian language dictionaries which illustrate the objectification of space in the linguistic picture of the world. The examined data, taken from linguistic dictionaries and encyclopaedic sources, allow the dynamics of the process of conceptualization and peculiarities of the categorization of space in the Russian-language mentality to be identified, and verify the formed hypotheses. The formats of the conceptualization of space (starting from an image and mental picture to the notion of frame) and the language dynamics of the objectification of these formats are discussed. Examples from dictionaries of the National Russian Corpora illustrate the objectification of the language world map most vividly. The analysed data from the linguistic dictionaries and encyclopaedic sources prove the working hypothesis by defining the set of attributes which define the concept SPACE, the dynamics of the conceptualization process, and peculiarities of the categorizatition of space in the Russian language mind. The conclusion is drawn that the concept SPACE is an integrated, multiple-aspect, conceptional compound which is connected with the categorization of reality. The basis of the categorization of space is the prototypical approach. In the Russian language world map, the prototype of SPACE is FIELD. Numerous new attributes of the word space show the broadening of the human idea about this universal phenomenon, which is already considered to be not only a form of substance existence, but also one of many forms of spiritual activities. The method of identifying the conceptional attributes is conceptually definitional analysis. Multidirectional tendencies to both widening and narrowing areas of space conceptualization were found, together with the tendency to integrate different formation-spaces.